A multifunctional and multiscale device of magnetic-controlled AND logical operation and detection based on the nonreciprocity of the magnetized InSb photonic structure - Si-Si Rao (Elsevier, 2021)
In this article, a multifunctional and multiscale device which can realize the functions of the magnetic-controlled AND logical operation and detection based on the one-dimensional magnetized InSb photonic structure is proposed and theoretically investigated. Properly modulating the target resonant absorption peak by the external magnetic field, and employing the peak to determine the logical operation, the accurate AND logical operation is fulfilled. Since the target absorption peak holds a superior quality factor value, the designed structure can be considered for detecting the crucial physical quantities, magnetic field, and refractive index. Especially, owing to the magneto-optical effect, time-reversal symmetry and space-reversal symmetry are broken, and the nonreciprocity is generated, which further makes the logical operations and detection of the forward and backward scales can be simultaneously acquired. Numerical analysis gains the optimal sensitivity, the quality value and detection limit. For the detection of magnetic field, and refractive index are 3.13 × 1012 T−1, 9341, 8.4 × 10−5 T, and 1.13 × 1011 RIU−1, 10537, 5.6 × 10−4 RIU, respectively. Surpassing the conventional electromagnetic devices, the designed photonic structure in this work with the combination of magnetic-controlled AND logical operation and detection functions plays a significant constructive role in information communication and photonic computing.